Hakikat Ilmu Pengetahuan dan Teknologi dalam Perspektif Epistemologi Islam - Cindy Dwi Julianti; Lailatus Sangadah; Siti Naila Arini; Alihan Satra (Advances In Education Journal, 2026)
In the Islamic view, science and technology (IPTEKS) are value-bound (not value-free), meaning they must be aligned with Islamic teachings. Science and Technology (IPTEKS) is the result of human thot and feeling, therefore it must be developed in accordance with the development of human intellect. The development of IPTEKS is part of fulfilling the obligations of humans as rational beings created by Allah. Science and technology are not merely means to achieve worldly progress, but also tools to draw closer to Allah. Islam views knowledge as an integral part of human life that should be directed toward the common good. The essence of knowledge in the Islamic perspective is not value-neutral; knowledge is seen as a means to know Allah SWT and to fulfilll the human duty as a caliph on earth. As for technology, it is the result of applying knowledge in human life. In Islam, technology is permitted and even encouraged as long as it is used for good and the common good. Thus, the essence of knowledge and technology in Islam lies in their unity with the values of monotheism, ethics, and humanitarian goals.